Strategi Pengelolaan Objek WisataPemandian Air Panas Dalam Meningkatkan Kunjungan Wisatawan Di Kecamatan Sipoholon - Remaida Panjaitan; Rusmauli Simbolon; Sudirman Lase; Yulia K S Sitepu; Tio R J Nadeak (Universitas Katolik Widya Karya Malang, 2023)
This research analyzes the management strategy for hot springs in Sipoholon sub-district with the aim of increasing tourist visits. Sipoholon sub-district has extraordinary natural potential, with stunning views and natural hot springs as the main attraction. This research uses qualitative research methods, namely direct field research and conducting observations and interviews. The hot springs located in Situmeang Habinsaran, Sipoholon District, North Tapanuli have become an inspiration for hot spring owners to open hot spring tourism, hot water flows with temperatures of 40 to 70 degrees Celsius make this place feel like another paradise on Indonesian soil. The results of this research are to find out the profile of the owner of the hot spring tourism object and how the management is carried out by the owner of the hot spring tourist attraction in Situmeang Habinsaran Village. The bath owner always prioritizes maintaining the cleanliness and comfort of the hot spring location. This hot spring is still natural from nature, the hot spring owner only needs to maintain beauty and cleanliness so that visitors feel comfortable while at the tourist location. Keywords: Aek Rangkat, Hot Springs, Tourism